Assessment of antifouling efficacy of polyhedral oligomeric silsesquioxane based poly (urea–urethane–imide) hybrid membranes. (25th July 2015) - Ajit Walter, P.; Muthukumar, T.; Reddy, B.S.R.
Abstract A series of polyhedral oligomeric silsesquioxane (POSS) based poly(urea–urethane–imide) (PUUI‐POSS) membranes were synthesized by varying the proportions of imide using 2, 4‐toluene diisocyanate (TDI) and bis(aminopropyl) terminated polydimethylsiloxane (PDMS). The molecular structures of poly(urea–urethane–imide)s were characterized by Attenuated total reflection Fourier transform infrared (ATR‐FTIR) spectroscopic technique. Incorporation of imide domain and its influence on surface roughness was investigated by atomic force microscopy (AFM). Hydrophobicity of polymeric membrane surfaces was determined by contact angle measurement. The thermal properties of the polymers were studied by thermogravimetric analysis. The antimicrobial activities and inhibition of bacterial attachment of these polymeric membranes were studied on Gram‐positive (Staphylococcus aureus) and Gram‐negative bacteria (Escherichia coli) by the disc‐diffusion method. Significance and Impact of the Study The antifouling performance has been evaluated for the polymeric membranes against two bacteria (Staphylococcus aureus (ATCC 6538)) (Escherichia coli (ATCC 8739)). The polymeric membranes were incorporated with imide moiety to improve thermal stability of the polymeric materials. The synthesized polymeric membranes have shown good morphological properties for better antifouling activities. This study found that these membranes are capable of preventing micro‐organisms besides offering excellent bio‐fouling resistance.